ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF THE PEEL EXTRACTS OF Luffa acutangula - A. NETHRA; M. POONKOTHAI* (The Journal of Research ANGRAU, 2020)
The study was conducted to evaluate the antimicrobial and phytochemical activities of the peel extracts of Luffa acutangula. The antimicrobial activity of aqueous, petroleum ether, acetone and chloroform peel extracts was tested against the selected bacterial and fungal isolates using agar well diffusion method. The results proved that the acetone extract exhibited maximum antimicrobial activity against the tested bacterial and fungal isolates when compared to chloramphenicol and flucanazole (standard antibiotics) respectively. Preliminary phytochemical screening was carried out in the acetone extract of L. acutangula which revealed the presence of secondary metabolites such as saponins, phenols, terpenoids, tannins, flavonoids, sterols, anthocyanin, carbohydrates and amino acids. The FT-IR analysis revealed the presence of hydroxyl, amines and carboxylic acids as functional groups in L. acutangula.